Development Interactive Learning Web for Mathematics at SMP - Putri, Lusi Permata Amira; Pebriantika, Leni; Susila, Heni Rita (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This study aimed to design and evaluate the feasibility of web-based interactive multimedia for mathematics learning using an instructional design approach. This study employed a Research and Development (R&D) method using the Lee and Owens instructional design model, which consists of analysis, design, development, implementation, and evaluation stages. The feasibility evaluation was conducted using formative evaluation, including expert validation, one-to-one evaluation, small group trials, and field trials. The subjects of this study consisted of material expert, instructional design expert, media expert, and ninth-grade junior high school students. Data were collected using questionnaires, interviews, and observations, and were analyzed using descriptive quantitative and qualitative techniques through percentage analysis. The results showed that the developed web-based interactive multimedia was categorized as very feasible in terms of validity, practicality, and usability. The multimedia was developed systematically through an instructional design process and integrated multimedia elements such as text, images, videos, animations, and interactive quizzes to support mathematics learning. The findings indicate that web-based interactive multimedia developed through instructional design and feasibility testing can be used as an instructional media to support interactive, flexible, and student-centered mathematics learning.